(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
Abstract. This article discusses the Newton-Coates formulas for the numerical integration of the Maple package, which have been discussed. In this study, for the purpose of numerical integration of trapezoidal method, Simpson method and Simpson 3/8 method, we examined. We analyzed the function f defined in the interval [a, b] at point f (x) by presenting several analyzes. The Maple package provides the latest applications of numerical analysis in a shorter and more efficient way, which has led to the solution of important scientific and technical problems today. With the help of Maple software, we solved our desired changes on its clear and reliable forms.